the Solving Partial Differential Equations by using Efficient Hybrid Transform Iterative Method - Ruaa Shawqi Ismael; Ali Al -Fayadh; Saad M. Salman (Tikrit Journal of Pure Science, 2024)
The aim of this article is to propose an efficient hybrid transform iteration method that combines the homotopy perturbation approach, the variational iteration method, and the Aboodh transform forsolving various partial differential equations. The Korteweg-de Vries (KdV), modified KdV, coupled KdV, and coupled pseudo-parabolic equations are given as examples to show how effective and practical the suggested method is. The obtained exact solitary solutions of the KdV equations as well as the exact solution of the coupled pseudo-parabolic equations are identified as a convergent series with easily calculable components. identified as a convergent series with easily calculable components.